Analisis Tipe Fluida Mata Air Panas berdasarkan Diagram Cl-SO4-HCO3 di Desa Pinaesaan Kabupaten Minahasa Selatan - Angely Syuly Ratag; Cyrke A.N. Bujung; Farly Reynol Tumimomor; Jeferson Polii (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2022)
Geothermal is a renewable energy source that occurs naturally beneath the earth's surface. This energy source comes from heating magma to rocks and water along with the elements contained in the earth's crust. North Sulawesi has the potential as a geothermal development area, either directly or indirectly. The research location in Pinaesaan Village has geothermal potential because it’s characterized by the presence of hot springs and is included in the Geothermal Work Area Kotamobagu. The purpose of this study was to determine the type of fluid and molecular functional groups of hot springs in Pinaesaan Village, South Minahasa Regency. By geochemical method using Cl-SO4-HCO3 diagram and FTIR, it’s known that the type of hot spring fluid in Pinaesaan Village is Chloride (Cl) type, and the molecular functional groups are C=O, where the constituents of the main chain C bind to Cl (Chloride) which corresponds to the result of fluid type.